Lower Arginine Bioavailability, Increased FeNO Levels, and Airway Resistance on Impulse Oscillometry Are Characteristics of Asthma in Children and Young Adults with Sickle Cell Disease - Aylin Kont Ozhan; Tugba Arikoglu; Melih Er; Selma Unal; Didem Derici Yıldırım; Funda Erkasar; Şenay Balcı; Lulufer Tamer; Semanur Kuyucu (Medicina, 2024)
Background and Objectives: Data on characteristics of asthma in children with sickle cell disease (SCD) is conflicting. Recently, the L-arginine pathway has gained attention in the pathogenesis of asthma and SCD. This study aimed to determine the distinctive clinical and laboratory features and the role of arginine metabolism in asthmatic children with SCD. Materials and Methods: A total of 52 children and adolescents with SCD, including 24 with asthma (SCD-A) and 28 without asthma (SCD-NA), and 40 healthy controls were included. A questionnaire, atopy tests, fractional exhaled nitric oxide (FeNO), and lung function tests were employed. Serum metabolites of the arginine pathway were measured. The results of the three groups were compared. Results: The demographic characteristics and atopy markers of the three groups were similar. FEV1%, FEV1/FVC, MMEF%, and total lung capacity (TLC%) values of SCD-A patients were not significantly different from the SCD-NA group, but they were significantly lower than the values measured in the controls. FeNO values greater than 35 ppb were present only in the SCD-A group. In impulse oscillometry, median resistance values at 5 Hz (R5)% were higher in both SCD subgroups than in healthy controls (p = 0.001). The (R5-20/R5)% values were higher in the SCD-A group (p = 0.028). Serum arginine levels and arginine bioavailability indices were significantly lower in the SCD-A group than in the SCD-NA group and healthy controls (p = 0.003 and p < 0.001). Conclusions: Asthma in children with SCD was not associated with atopy or low FEV1/FVC levels. However, lower arginine bioavailability and higher FeNO levels differentiated asthma in patients with SCD. High R5% and (R5-20/R5)% values indicated increased airway resistance in SCD, with a predominance of small airway disease in asthmatics.